Facile Subsequently Light-Induced Route to Highly Efficient and Stable Sunlight-Driven Ag−AgBr Plasmonic Photocatalyst - Kuai, Long; Geng, Baoyou; Chen, Xiaoting; Zhao, Yanyan; Luo, Yinchan (Langmuir, 2010)
In this paper, we successfully fabricate a stable and highly efficient direct sunlight plasmonic photocatalyst Ag−AgBr through a facile hydrothermal and subsequently sunlight-induced route. The diffuse reflectance spectra of Ag−AgBr indicate strong absorption in both UV and visible light region. The obtained photocatalyst shows excellent sunlight-driven photocatalytic performance. It can decompose organic dye within several minutes under direct sunlight irradiation and maintain a high level even though used five times. In addition, both the scanning electron microscopy images and X-ray photoelectron spectroscopy dates reveal the as-prepared photocatalyst to be very stable. Moreover, the mechanism suggests that the high photocatalytic activity and excellent stability result from the super sensitivity of AgBr to light, the surface plasmon resonance of Ag nanoparticles in the region of visible light, and the complexation between Ag+ and nitrogen atom. Thus, the facile preparation and super performance of Ag−AgBr will make it available to utilize sunlight efficiently to remove organic pollutants, destroy bacteria, and so forth.